Pengaruh Brand Image dan Price terhadap Keputusan Repurchase Order pada Produk Skincare Skintific Peeling Serum di Jakarta - Aldyas Az-Zahra; Purwatiningsih Purwatiningsih (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the influence of brand image and price on the decision to repurchase skincare products Skintific peeling serum in Jakarta. The research method used was descriptive quantitative with data collection techniques through questionnaires distributed to 127 respondents who had used the product. In addition to questionnaires, data was also collected through observation, interviews, and documentation. Data analysis was carried out partially and simultaneously to test the influence of each independent variable on repurchase decisions. The results showed that brand image had a positive and partially significant influence on repurchase decisions, with a significance value of 0.000 < 0.05 and a calculated t-value of 3.712 > t table 1.6572. The price also shows a positive and partially significant influence with a significance value of 0.000 < 0.05 and a calculated t-value of 7.084 > t of the table of 1.6572. Simultaneously, brand image and price have a significant effect on repurchase decisions, with a significance value of 0.000 < 0.05 and a value of f calculated 126.316 > f table 3.07. These findings underscore the importance of brand image management strategies and competitive pricing in increasing customer loyalty. This research is expected to make a practical contribution to companies in designing marketing and product development strategies that are more effective and oriented towards consumer satisfaction.